Household Financial Management of Palm Sugar Farmers Amid Declining Sap Production and Income Instability in Bonto - Salsabila Salsabila; Wa Ode Rayyani (Jurnal Studi Multidisiplin Ilmu, 2025)
Purpose: This study analyzes the household financial management strategies of palm sugar farmers facing income instability caused by the structural decline in sap production in Bonto Salama Village, West Sinjai Subdistrict, Sinjai Regency.Research Methodology: A descriptive qualitative approach was employed using a single embedded case study. Data were collected through in-depth interviews, participatory observation, and documentation involving one husband-and-wife pair of palm sugar farmers with at least three years of tapping experience, selected through purposive sampling. Data were analyzed using the Miles, Huberman, and Saldana interactive model, while credibility was ensured through source and technique triangulation and member checking.Results: Farmers experienced unstable income due to declining palm productivity as trees aged. To maintain household financial stability, they reduced consumption, diversified income through vegetable cultivation and collecting dried clove leaves, and relied on social capital by borrowing from relatives and participating in rotating savings groups.Conclusions: Household financial management remains informal and experience-based, with social capital serving as the primary financial buffer during periods of income instability.Limitations: The findings are based on a single informant pair from one village, limiting broader generalizability. Contributions: This study enriches the household finance literature by providing empirical evidence of adaptive financial strategies employed by palm sugar farmers in Indonesia's informal agricultural sector under persistent income uncertainty.